Upaya Peningkatan Standar Mutu Standar Mutu Pendidikan di SMA Al-Hidayah Medan - Akmalia, Rizki; Syahkila Simangunsong, Arimbi; Azzahrah, Nindya; Halawa, Syafitri; Sahrani Sibarini, Wardah (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Improving the quality standards of education in schools is an important struggle in achieving the goal of quality and equitable education. The techniques in collecting this data are observation, interview, and documentation. This research aims to find out the various efforts and strategies that have been implemented to ensure that students receive quality and relevant education. The article discusses several measures to improve the quality of education in schools, including curriculum improvement, teacher training, stakeholder participation, the use of technology and careful monitoring. With a strong commitment and a systematic approach, quality education can become more accessible to all students, creating a smarter and more competitive society